EXPERIMENTAL AND CALCULATION-BASED FORECASTING OF FUEL CONSUMPTION ON ZINCBEARING SLAG PROCESSING UNIT BASED ON PHASE INVERSION REACTOR - B. Dikhanbayev; K. Baubekov; A. Dikhanbayev (European Scientific Journal, ESJ, 2014)
Using the afine (related) modeling, which foresee, based on test data of pilot plant, the necessity of correct calculation of conditional sample, is performed recalculation of pilot plant’s test results on industrial sample. Having defined more precisly in mathematical description of process collection accountable factors, the list of basic numbers of similarity were obtained, on the basis of which is developed new technique of calculated estimation of fuel consumption in industrial sample of pilot plant. As a result of calculations it is shown that in comparison with fuming-furnace processing the liquid slag, on industrial sample of pilot plant the consumption of natural gas will be in two times lower, and with the increase of installation output in the range (5-25) t/h the specific consumption of natural gas will reduce in ~1, 5 times.